Clostridium Perfringens Epsilon Toxin Binds to Membrane Lipids and Its Cytotoxic Action Depends on Sulfatide. - Carles Gil; Jonatan Dorca-Arévalo; Juan Blasi (PLoS ONE, 2015)
Epsilon toxin (Etx) is one of the major lethal toxins produced by Clostridium perfringens types B and D, being the causal agent of fatal enterotoxemia in animals, mainly sheep and goats. Etx is synthesized as a non-active prototoxin form (proEtx) that becomes active upon proteolytic activation. Etx exhibits a cytotoxic effect through the formation of a pore in the plasma membrane of selected cell targets where Etx specifically binds due to the presence of specific receptors. However, the identity and nature of host receptors of Etx remain a matter of controversy. In the present study, the interactions between Etx and membrane lipids from the synaptosome-enriched fraction from rat brain (P2 fraction) and MDCK cell plasma membrane preparations were analyzed. Our findings show that both Etx and proEtx bind to lipids extracted from lipid rafts from the two different models as assessed by protein-lipid overlay assay. Lipid rafts are membrane microdomains enriched in cholesterol and sphingolipids. Binding of proEtx to sulfatide, phosphatidylserine, phosphatidylinositol (3)-phosphate and phosphatidylinositol (5)-phosphate was detected. Removal of the sulphate groups via sulfatase treatment led to a dramatic decrease in Etx-induced cytotoxicity, but not in proEtx-GFP binding to MDCK cells or a significant shift in oligomer formation, pointing to a role of sulfatide in pore formation in rafts but not in toxin binding to the target cell membrane. These results show for the first time the interaction between Etx and membrane lipids from host tissue and point to a major role for sulfatides in C. perfringens epsilon toxin pathophysiology.